GE_GERICHTE P/4741/2021 vom 29. August 2023 - GE Cour de justice (2023)
VOIES DE FAIT;LÉSION CORPORELLE SIMPLE;CONTRAINTE(DROIT PÉNAL);TENTATIVE(DROIT PÉNAL);ACCÈS INDU À UN SYSTÈME INFORMATIQUE;MENACE(DROIT PÉNAL) | CP.123; CP.181; CP.126; CP.22; CP.180; CP.143bis; CP.42; CPP.429; CPP.433; CP.34